2020
DOI: 10.1016/j.molmet.2020.101080
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon acutely regulates hepatic amino acid catabolism and the effect may be disturbed by steatosis

Abstract: Objective Glucagon is well known to regulate blood glucose but may be equally important for amino acid metabolism. Plasma levels of amino acids are regulated by glucagon-dependent mechanism(s), while amino acids stimulate glucagon secretion from alpha cells, completing the recently described liver-alpha cell axis. The mechanisms underlying the cycle and the possible impact of hepatic steatosis are unclear. Methods We assessed amino acid clearance in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 72 publications
(114 reference statements)
6
91
0
Order By: Relevance
“…Previous studies have revealed that GCGR blockade decreased hepatic amino acid catabolism and increased the serum amino acid level, revealing the important role of GCGR in regulating amino acid metabolism (Solloway et al, 2015 ; Dean et al, 2017 ; Galsgaard et al, 2018 ; Winther-Sorensen et al, 2020 ). In our study, the KEGG pathway analysis also indicated that 11 pathways were enriched in amino acid metabolism, which was in the second place of metabolism-related pathways ( Figure 2C ).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Previous studies have revealed that GCGR blockade decreased hepatic amino acid catabolism and increased the serum amino acid level, revealing the important role of GCGR in regulating amino acid metabolism (Solloway et al, 2015 ; Dean et al, 2017 ; Galsgaard et al, 2018 ; Winther-Sorensen et al, 2020 ). In our study, the KEGG pathway analysis also indicated that 11 pathways were enriched in amino acid metabolism, which was in the second place of metabolism-related pathways ( Figure 2C ).…”
Section: Resultsmentioning
confidence: 98%
“…GCGR blockade–induced hyperaminoacidemia has also been documented in mammals, from mice, monkey, to human patients (Okamoto et al, 2015 ; Larger et al, 2016 ; Galsgaard et al, 2018 ; Li et al, 2018 ). Studies further revealed that plasma hyperaminoacidemia was due to the decreased liver amino acid catabolism after GCGR inhibition (Solloway et al, 2015 ; Kim et al, 2017 ; Winther-Sorensen et al, 2020 ). High levels of plasma amino acids in turn stimulated the pancreatic α-cell hyperplasia, which has been defined as the liver-α cell axis (Dean et al, 2017 ; Galsgaard et al, 2018 ; Wewer Albrechtsen et al, 2018a ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations